2000
DOI: 10.1258/0022215001904635
|View full text |Cite
|
Sign up to set email alerts
|

Influence of human wet cerumen on the growth of common and pathogenic bacteria of the ear

Abstract: The available data on the effect of human wet cerumen on bacterial growth are not conclusive. Nevertheless it is widely accepted that cerumen has a bactericidal effect. In this study the activity of human wet cerumen on bacterial growth was assessed by applying cerumen suspensions to bacterial cultures. Bacterial counts were performed before and after application of cerumen suspensions. A total of 383 assays was carried out with 73 pools of cerumen that were tested against cultures of Staphylococcus aureus, St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
3
11
1
1
Order By: Relevance
“…[7,14] However other studies have reported a lack of bactericidal eff ect of cerumen on P. aeruginosa. [15,16,19] Megarry et al, and Lum et al, studied the mycocidal eff ect of cerumen consistent with our study. [7,9] Interestingly, our study shows that the human cerumen has more antibacterial property as compared to antifungal property.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…[7,14] However other studies have reported a lack of bactericidal eff ect of cerumen on P. aeruginosa. [15,16,19] Megarry et al, and Lum et al, studied the mycocidal eff ect of cerumen consistent with our study. [7,9] Interestingly, our study shows that the human cerumen has more antibacterial property as compared to antifungal property.…”
Section: Discussionsupporting
confidence: 90%
“…[12] Our fi ndings on the bactericidal eff ect of cerumen on E. coli are consistent with Stone and Fulghum, Chai and Chai and Bauman et al, [13][14][15] However, Lum et al, and Campos et al, found insignifi cant bactericidal eff ect and stated that Escherichia coli is not a normal commensal of the ear canal, and thus may not be recognized by the immune system of the ear canal. [7,16] Campos et al, showed that an increase in growth occurred much more frequently than a decrease in growth in almost every microorganism tested with wet cerumen, with the mean increase percentage being much higher than the mean decrease percentage, except in the case of S. aureus. [16] Burtenshaw reported inconsistent bactericidal activity of cerumen against S. aureus.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The argumentation against a bactericidal activity are based on the consideration that the rich nutrients of ear wax enable bacteria and fungi to grow [57][58][59][60][61]. On the other hand there are several reports describing an antimicrobial effect of ear wax with an effect against a wide range of bacteria including Haemophilus influenzae, Staphylococcus aureus, Escherichia coli and fungi [61][62][63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…Some anti-fungal activity was shown against Candida albicans and C. parapsilosis [15,16], common ear fungal pathogens [17]. Nevertheless, these results were challenged by the finding that fresh cerumen hosts many bacteria and fungi [2,20,24], with bacterial counts as high as 10 7 g -1 cerumen [3], and recently by the observation that human cerumen is more likely to increase than to decrease the growth of many bacteria [4], putting the antimicrobial properties of cerumen under further doubt. Here we demonstrate that it could host, and its components (proteins, lipids, and cholesterol) could serve as food sources for multiple bacterial species.…”
Section: Introductionmentioning
confidence: 99%